Czy naturalne procesy ekologiczne w juwenilnej fazie rozwoju drzewostanu założonego sztucznie różnicują jego strukturę przestrzenną? - Szmyt, Janusz; Korzeniewicz, Robert (Leśne Prace Badawcze, 2014)
Structural diversity is one of the most interesting phenomena that have been studied by forest ecologists and practitioners. Amongst the different characteristics of forest structure, spatial diversity of trees and their attributes seem to be very important. The more spatially structured a population is, the higher its diversity in terms of size and species richness. Because most forests in Europe are managed and were artificially established, they are subjected to conversion processes turning them into more complex systems. The approach presented here aims at elucidating whether natural processes, such as self-thinning, can cause the self-differentiation of spatial structure in artificially planted stands. Our analyses focused on untended Scots pine and pedunculate oak stands in the juvenile phase of development and were based on spatially explicit structural indices for positioning and size differentiation (diameter, total height and crown length). The obtained results indicate that live trees were dispersed more or less regularly. Unlike the angle- based index, which mostly indicated randomness in tree location, a distance-based index showed clear regularity. We also found that the distribution of tree attributes auto-correlates to tree location as indicated by significantly lower index values compared to values resulting from random reassignment of the examined attributes. This low degree of spatial differentiation is further confirmed by the distribution of indices in differentiation classes. Our results allow us to conclude that, in the case of light demanding species (pine and oak), natural processes do not increase spatial diversity of the stand, although, both species showed a certain degree of deviation in this respect.